2010
DOI: 10.1109/tps.2010.2045903
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency Improvement of Nitric Oxide Treatment Using Nanosecond Pulsed Discharge

Abstract: Pulsed streamer discharge plasmas, one of the non-thermal plasma have been used to treat exhaust gases. Since a pulse width of applied voltage has a strong influence on the energy efficiency of the removal of pollutants, the development of a short pulse generator is of paramount importance for practical applications. In this work, nano seconds (ns) pulse generator which has 5ns of pulse duration in output pulsed voltage is developed and NO removal experiments using ns pulsed discharge were conducted. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…Overall, researchers have noted that the pulse duration of the applied high-voltage pulse has a significant influence on the radical yield; shorter pulses result in higher yields [16,22,17,18]. To study and understand this phenomenon, we have developed a flexible nanosecond pulse source that produces (sub)nanosecond pulses [24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, researchers have noted that the pulse duration of the applied high-voltage pulse has a significant influence on the radical yield; shorter pulses result in higher yields [16,22,17,18]. To study and understand this phenomenon, we have developed a flexible nanosecond pulse source that produces (sub)nanosecond pulses [24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…2 Electric discharge plasma has been widely studied as a low cost and high energy efficiency exhaust gas treatment method in recent years [9][10][11]. However, more improvements are still required, especially in energy consumption, to make this technology viable in commercial use [1].…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that using a real diesel exhaust gas increased the ability of NTP in removing NOx due to the presence of carbonaceous soot. In 2010, Matsumoto et al [10] developed a nano-second pulse generator and indicated that a shorter pulse duration showed a great improvement in energy efficiency of NO removal. The gas cylinders of N2 and NO in N2 were used to simulate the exhaust gas.…”
Section: Introductionmentioning
confidence: 99%
“…The energy needed to remove NO through individual MEO and MER processes found to be 0.221 g/kWh and 0.769 g/kWh respectively (Table I middle column). At the same time, the NO removal energy efficiency become higher 0.99 g/kWh (Table I middle column) when combined the MEO & MER processes, which is almost 10 times lower than the energy efficiency obtained for NO removal by nanosecond pulsed discharge (12 g/kWh) 38 and non-thermal discharge (∼20 g/kWh) 39 methods. Noteworthy here that the high installation cost of nanosecond pulsed discharge and non-thermal discharge methods makes the present electrochemical (installation cost is very less) approach more economical.…”
mentioning
confidence: 79%